Outcome following radiotherapy for head and neck basal cell carcinoma with 'aggressive' features. (September 2017) - Rishi, Anupam; Hui Huang, Shao; O'Sullivan, Brian; Goldstein, David P; Lu, Lin; Ringash, Jolie; Waldron, John; Wells, Woody; Sun, Alex; Hope, Andrew; Chung, Peter; Giuliani, Meredith; et al.
Highlights: Aggressive head-and-neck basal cell carcinoma (HN-BCC) has higher relapse. Radiotherapy (RT) is an effective treatment for aggressive HN-BCC. Definitive RT provides an alternative effective option if surgery is not used. Factors with risk of relapse: recurrent disease, H-zone primary, size, stage. Abstract: Objectives: The literature demonstrates that 'aggressive' head-and-neck basal cell carcinomas (HN-BCC) have a higher than expected relapse rate with unfavorable outcomes. We report outcomes following definitive (dRT) or post-operative radiotherapy (PORT) for these tumors. Methods: We reviewed all HN-BCC patients with 'aggressive' features (primary lesions diameter >10 mm, >2 recurrences, or extra-cutaneous extension), treated with megavoltage dRT or PORT between 1998 and 2013. Loco-regional control (LRC) and relapse-free survival (RFS) were estimated using the competing risk method, and overall survival (OS) by Kaplan-Meier method. Univariable analysis explored factors associated with relapse. Results: A total of 108 histologically confirmed 'aggressive' HN-BCC patients were identified, including 38 (35%) presenting de novo and 70 (65%) treated for recurrence (rBCC). dRT was offered to 72 (66.7%) patients and PORT to 36 (33.3%). Median follow-up was 3.5 years. Actuarial 3-year LRC, RFS, and OS were 87% (95% confidence interval: 77–92), 82% (72–89), and 87% (80–94), respectively. LRC rates for dRT and PORT were similar [hazard ratio (HR) 0.61 (0.17–2.23), p = 0.46]. Factors associated with higher risk of relapse were: rBCC [HR 7.96 (1.03–61.71), p = 0.047], 'H-zone' (mid face, eyes, and ears) location [HR 3.13 (1.07–9.19), p = 0.04], tumor size [HR 1.32 (1.08–1.6), p = 0.006], nodal involvement [HR 3.68 (1.11–12.2), p = 0.03] and stage [HR 3.13 (1.19–8.26), p = 0.02]. Conclusion: RT is an effective treatment for 'aggressive' HN-BCC when used as a definitive modality or as PORT. Non-surgical management with definitive radiotherapy provides an alternative effective option if surgery is not used.